Tantangan dan strategi manajemen risiko dalam menghadapi pembiayaan bermasalah (NPF) pada Bank Syariah - Farika, Alya (Maliki Interdisciplinary Journal, 2026)
This study aims to analyze the challenges and risk management strategies in dealing with non-performing financing (NPF) in Islamic banks. This research employs a qualitative descriptive approach using a literature review method based on national and international journals, including publications from UIN Maulana Malik Ibrahim Malang. The results indicate that non-performing financing is one of the major risks faced by Islamic banks, which can affect financial stability and overall performance. The challenges arise from internal factors such as weak financing analysis and monitoring, as well as external factors such as economic conditions and customer moral hazard. Risk management strategies implemented include the 5C analysis, continuous monitoring of financing, and financing restructuring, which have proven effective in reducing NPF levels and maintaining asset quality.